Polimorfismo R72P do gene TP53 no câncer colorretal : metanálise - (:unkn) unknown (Universidade Estadual de Goiás, 2014)
The meta-analysis has the objective to correlate the TP53 R72P polymorphism with colorectal cancer analyzing the data produced by researchers in the world. This meta-analysis comparing global data 3 continents America, Europe and Asia, and the results were compared globally, and also divided by continents. The project included a total of 4338 cases of CRC genotyped for codon R72P. Studies from all over the world and after a thorough systematic review of the literature on the track work p53 in tumorigenesis and the statistical analysis, it is concluded that the polymorphic alleles that produce homozygous arginine or arginine heterozygous / proline are considered the predisposing factors for the emergence of CCR.
Keywords: Câncer colorretal; Códon R72P; Polimorfismo e TP53; Colorectal cancer; Codon R72P; Polymorphism and TP53; CIENCIAS BIOLOGICAS; QUIMICA::QUIMICA ORGANICA